Activity of Corilagin on Post-Parasiticide Liver Fibrosis in Schistosomiasis Animal Model. (January 2013) - Huang, Y.-F.; Zhang, S.-L.; Jin, F.; Cheng, D.; Zhou, Y.-P.; Li, H.-R.; Tang, Z.-M.; Xue, J.; Cai, W.; Dong, J.-H.; Zhao, L.
This study investigates the effects and possible molecular mechanisms of corilagin extraction on prevention of Schistosoma japonicum ova-induced granulomas and liver fibrosis. As a result, under a light microscope, when compared to a model group, the corilagin group showed smaller granulomas, less liver cell denaturation and less inflammatory cell infiltration, and the connective tissues were significantly decreased. By Masson staining, the liver sections from the corilagin group showed less collagen distributed around granulomas, decreased liver fibrosis in the portal tracts and less formed interlobular tissue. The expression of hydroxyproline, IL-13 in liver and GATA3 in spleen in the model group was significantly higher than that in the normal group (P<0.05 or 0.01), while the level of hydroxyproline, IL-13 and GATA3 in the corilagin group were significantly lower than that in the model group (P<0.05). In conclusion, corilagin extraction can decrease the level of Th2-associated profibrotic cytokine IL-13, and down-regulate the transcription of GATA3 mRNA in spleen cells, which alleviate the hepatic fibrosis caused by egg granuloma in Schistosoma japonicum infection.